Differential association theory reconsidered: An extension and its empirical test - Bruinsma, Gerben (Journal of quantitative criminology, 1992)
In 1974 the German methodologist Karl-Dieter Opp expounded and expanded Sutherland's differential association theory. In this article an empirical test of this version of the theory is presented based on data for 1196 boys and girls in the age range 12 to 17 years. Furthermore, some new and additional theoretical specifications about the social influence of others on the individual, all in accordance with the original ideas of Sutherland, are proposed and empirically tested. The differential association theory according to the version of K.-D. Opp is fairly well corroborated by the data. Only three of the postulated relationships are rejected. The theory explains 51% of the variance of criminal behavior, even considering that no “criminal” population is used for the test and only minor offenses are measured. The test also shows that the impact of the frequency of contacts with deviant behavior patterns on the development of positive definitions and on the frequency of communication about relevant techniques is substantial and cannot be ignored by criminologists. Furthermore, special analyses show that several propositions favor the theory. It is the deviancy of others that has the most substantial impact: the more youngsters have contact with their friends, the stronger the impact of the deviancy of their friends on the development of positive definitions or on the frequency of communication about techniques. The tests also show that the more youngsters identify themselves with others, the stronger will be the impact of the deviancy of the others on their norms. These results support the modification of the DA theory according to Opp and falsify some propositions of social control theory.